The rise and ongoing legacy of localism as collective identity in Hong Kong: Resinicisation anxieties and punishment of political dissent in the post-colonial era - Adorjan, Michael (Punishment & society, 2021)
China’s new National Security Law, enacted in Hong Kong on 30 June 2020, has amplified widespread concerns among the city’s population regarding the implications of this law. These concerns have at root anxieties related to Hong Kong’s resinicisation, referring to anxieties over Hong Kong's political and economic dependence on mainland China, including loyalty and patriotism towards the motherland. This paper explores these developments in relation to the ongoing legacy of localism, argued to be instilled as a colonial project to help secure the populations’ identification with Hong Kong. Seen as ‘criminals’ from the perspective of mainland Chinese authorities, many of those involved in today's protests (many of whom include young people) see themselves as engaging in legitimate forms of civil disobedience. First explicating the context of Hong Kong's colonial history in order to help make sense of present-day turmoil, we turn to recent trends in arrests related to the protests, as well as evidence of rapidly declining trust in the Hong Kong Police Force, seen by some as increasingly beholden to the interests of mainland China. Implications for these trends going forward are considered, with a discussion of the need for greater attention to colonial histories and post-colonial ramifications.